2013
DOI: 10.1097/scs.0b013e3182646126
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Malignant Transformation in Craniomaxillofacial Fibrous Dysplasia

Abstract: Spontaneous malignant transformation in craniomaxillofacial fibrous dysplasia (FD) is extremely rare and its clinicopathological characteristics remain largely unknown. Here, we aimed to characterize the epidemiology and clinicopathological features of malignancies arising from preexisting FD by presenting data from a Chinese tertiary referral hospital and review of English and Chinese literatures. The craniomaxillofacial disease registry of Shanghai Ninth People's Hospital was searched and reviewed to collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 10 publications
0
37
1
Order By: Relevance
“…Thus, our patients are being regularly monitored because of the need for additional craniofacial bone surgical interventions and risks of progression, recurrence, appearance of new dysplastic bone lesions, and/or malignant degeneration. 1,2,12,34 Despite these limitations, we believe that the present study along with objective assessment of the results provides additional information that will broaden the field of knowledge of surgical outcomes of craniofacial fibrous dysplasia patients. Further research may confront or ratify our data and try to solve these drawbacks.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, our patients are being regularly monitored because of the need for additional craniofacial bone surgical interventions and risks of progression, recurrence, appearance of new dysplastic bone lesions, and/or malignant degeneration. 1,2,12,34 Despite these limitations, we believe that the present study along with objective assessment of the results provides additional information that will broaden the field of knowledge of surgical outcomes of craniofacial fibrous dysplasia patients. Further research may confront or ratify our data and try to solve these drawbacks.…”
Section: Discussionmentioning
confidence: 92%
“…Yearly X-rays are advocated for screening, and patients must be educated to seek prompt medical attention upon experiencing a sudden change in the quality or severity of their symptoms. Treatment options for sarcomatous transformation of FD include conventional chemotherapy, in addition to radical resection if the tumor location is amenable to surgical excision [8]. …”
Section: Discussionmentioning
confidence: 99%
“…18 Malignant transformation generally occurs in <1% of patients with FD, with the osteosarcoma being the most common histopathological type. 4,19 In a review of all cases of malignant transformation of craniomaxillofacial FD, Cheng et al 19 found a total of 38 cases in the past 2 decades. 4,19 In a review of all cases of malignant transformation of craniomaxillofacial FD, Cheng et al 19 found a total of 38 cases in the past 2 decades.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 The interval between initial FD and subsequent malignancy is variable, but rarely seen before 2 decades. 4,[18][19][20] The role of radiotherapy in FD transformation remains controversial as some authors supported its pathogenic importance, while others question it. Osteosarcoma was the most common type of neoplasm identified, accounting for 65.6% of all cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation